PENURUNAN TINGKAT HUNIAN INDEKOS DI MEDAN PADA TAHUN 2020: APAKAH BERKAITAN DENGAN PANDEMI COVID-19? - Kristian Agung Prasetyo; Merry Vierce Purba (JURNAL INFO ARTHA, 2023)
The research reported in this paper seeks to understand the association between the severity of Covid-19 infection and vacancy rate of boarding rooms in several districts Medan. Covid-19 infection was known to carry undesirable impacts to the economic condition. It forced academic institutions to use embrace distance learning in their daily teaching activities. Theoretically, this leads to an increase in the vacancy rate in boarding rooms used by students. However, it is interesting that Covid-19 infection rate does not have a significant correlation with vacancy rate in the areas being studied. Room rental rate, on the other hand, has a significant and positive link with room vacancy rate. It seems that room renters are more sensitive towards price than virus infection particularly when income is severely affected by the pandemi.